Seepage losses in the Coleambally Irrigation Area – loss estimates from channel automation data. Issue 1 (2nd January 2016) - Moavenshahidi, A.; Smith, R.; Gillies, M.
Abstract: Seepage from open channels is a major source of water loss across all irrigation districts in Australia. Pondage tests are acknowledged as the best direct method for seepage measurement, and the recorded water-level data from automated systems during periods of gate closure can be treated as pondage test data. A computer model that applies pondage test methodology to automated channel control data during periods of shut down in order to estimate seepage rates in different channel reaches was developed recently by the authors. They also applied the model to the total channel control (TCC) data for the entire Coleambally Irrigation Area (CIA) during 2009–2012, and seepage rates for each depth gauge, pondage and pool were estimated. In this paper, the estimated seepage rates from the channel automation data are used to (i) estimate likely seepage rates under operational conditions and (ii) estimate total annual volumes of seepage loss. Comparison with seepage estimates from previous seepage studies in the CIA showed reasonable agreement between estimated seepage rates from channel automation data and the estimates from previous studies. Importantly, the TCC data identified a number of channels with high seepage rates that were not identified in the previous seepage surveys.